Exploratory analysis of epidemiological and clinicopathological characteristics of soft tissue sarcomas: a single institutional study in Chennai - Parai, Shaoni; Ramkumar, B.; Raja, G.; J. G., Atul; Sharma, Manish Kumar; Narasimman, Vasanth Rooban (International Journal of Research in Medical Sciences, 2024)
Background: Soft tissue sarcomas (STS) from mesenchymal origin form diverse and complex group. Gastrointestinal stromal tumors (GIST)s are most common mesenchymal neoplasm of gastrointestinal system. Better comprehension of clinicopathological profile needed to improve overall prognosis. The objective is to study the epidemiological, clinicopathological characteristics, treatment outcome and other prognostic factors predicting overall survival (OS) and progression free survival (PFS) in STS. Methods: This study was conducted in Medical Oncology Department, Govt Royapettah Hospital, Chennai. It is a retrospective study, data retrieved from recorded files of patients with soft tissue sarcomas presented from Jan 2017-Dec 2021, and two years follow up data collected till Dec 2023. Results: In this study 92 patients with soft tissue sarcoma were analysed. Most commonly found histological subtype was GIST (29.3 %). In our study OS rate at 2 years (years) was 0.80. PFS rate at 2 years was 0.70. Surgical status, staging showed correlation with PFS in GIST in cox regression analysis and both PFS, OS in non-GIST sarcomas. In non-GIST sarcomas grade had correlation with PFS and Staging found as an independent factor associated with PFS. Site of primary in GIST and histopathology in non-GIST STS also showed correlation. Conclusions: In this study median OS and PFS not reached till the last date of follow up. Surgical status and staging found to be significant prognostic factors for both GIST and non-GIST sarcomas and grade in non-GIST sarcomas.